Extracellular chloride is required for efficient platelet aggregation. (2nd January 2018) - Taylor, Kirk A.; Wilson, Darren G. S.; Harper, Matthew T.; Pugh, Nicholas
Abstract: Anion channels perform a diverse range of functions and have been implicated in ATP release, volume regulation, and phosphatidylserine exposure. Platelets have been shown to express several anion channels but their function is incompletely understood. Due to a paucity of specific pharmacological blockers, we investigated the effect of extracellular chloride substitution on platelet activation using aggregometry and flow cytometry. In the absence of extracellular chloride, we observed a modest reduction of the maximum aggregation response to thrombin or collagen-related peptide. However, the rate of aggregation was substantially reduced in a manner that was dependent on the extracellular chloride concentration and aggregation in the absence of chloride was noticeably biphasic, indicative of impaired secondary signaling. This was further investigated by targeting secondary agonists with aspirin and apyrase or by blockade of the ADP receptor P2Y12. Under these conditions, the rates of aggregation were comparable to those recorded in the absence of extracellular chloride. Finally, we assessed platelet granule release by flow cytometry and report a chloride-dependent element of alpha, but not dense, granule secretion. Taken together these data support a role for anion channels in the efficient induction of platelet activation, likely via enhancement of secondary signaling pathways.